Seroprevalence and Biomarkers Detection of Human Herpes Virus (HHV-8) in Patients with Kaposi Sarcoma - Abdulrazzaq Neamah Zghair; Sumayah Faruq Kasim; Nazar Sh. Mohammed; Anil K. Sharma (Journal of Techniques)
Kaposi's sarcoma (KS) represents the most prevalent malignancy among untreated HIV-positive individuals. Herpesvirus linked with Kaposi's sarcoma (KSHV; also termed as human herpesvirus 8 (HHV8)). In this study, blood samples were collected from 120 individuals, 60 of them had HHV-8 infection with kaposi sarcoma and 60 persons as apparently healthy control. These patients attended Baghdad Teaching Hospital from the period of 15th February 2021 to 15th January 2022.